Strategi Kepala Sekolah dalam Meningkatkan Akreditasi di UPTD SMP Negeri 1 Kapur IX - Witri Octary Nanda; Hadiyanto Hadiyanto; Ermita Ermita; Sulastri Sulastri (Journal of Educational Administration and Leadership, 2022)
This study aims to find out the principal's strategy or plan to improve accreditation, what factors help and hinder the growth of accreditation, and what are the positive impacts of the principal's strategy to increase accreditation. Qualitative descriptive method is the method used in this study. In this study, data were collected through the use of data collection procedures such as observation, interviews and documentation. Data reduction is used to analyze and interpret facts, and narrative writing is used to communicate data and develop conclusions. The principal's approach to expanding accreditation, including raising eight national education standards, is the result of this study. Teachers, curriculum and learning, buildings and infrastructure, and support from the school community, such as committees, all help improve accreditation. Meanwhile, poor student achievement, low teacher performance, inadequate facilities, and limited education costs have all hindered the growth of accreditation. The good result is that facilities and infrastructure have improved, teacher performance has begun to improve, and the cost of education in schools can be reduced.